2015
DOI: 10.1590/s1517-838246320131291
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone resistance and ornithine decarboxylation activity in lactose-negative <italic>Escherichia coli</italic>

Abstract: Quinolones and fluoroquinolones are widely used to treat uropathogenic Escherichia coli infections. Bacterial resistance to these antimicrobials primarily involves mutations in gyrA and parC genes. To date, no studies have examined the potential relationship between biochemical characteristics and quinolone resistance in uropathogenic E. coli strains. The present work analyzed the quinolone sensitivity and biochemical activities of fifty-eight lactose-negative uropathogenic E. coli strains. A high percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Apart from tetrathionate respiration, the metabolic profile of EcoFA807‐17 differs from commensal strains of E. coli in several ways. It does not decarboxylate lysine or ornithine which are known virulence factors among Escherichia/Shigella genomospecies (Casalino et al, 2003; Gomig et al, 2015; Maurelli et al, 1998), although it demonstrates Indole production, a trait long known to be typical of E. coli but much less common with Shigella (Rezwan et al, 2004) and certain other members of Enterobacteriaceae. Its sugar utilization resembles Shigella in being unable to metabolize lactose, sucrose, and xylose (Taylor, 1965).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from tetrathionate respiration, the metabolic profile of EcoFA807‐17 differs from commensal strains of E. coli in several ways. It does not decarboxylate lysine or ornithine which are known virulence factors among Escherichia/Shigella genomospecies (Casalino et al, 2003; Gomig et al, 2015; Maurelli et al, 1998), although it demonstrates Indole production, a trait long known to be typical of E. coli but much less common with Shigella (Rezwan et al, 2004) and certain other members of Enterobacteriaceae. Its sugar utilization resembles Shigella in being unable to metabolize lactose, sucrose, and xylose (Taylor, 1965).…”
Section: Resultsmentioning
confidence: 99%
“…T A B L E 3 Biochemical phenotype of EcoFA807-17 compared with E. coli (ATCC 10536) et al, 2003;Gomig et al, 2015;Maurelli et al, 1998), although it demonstrates Indole production, a trait long known to be typical of E. coli but much less common with Shigella (Rezwan et al, 2004) and certain other members of Enterobacteriaceae. Its sugar utilization resembles Shigella in being unable to metabolize lactose, sucrose, and xylose (Taylor, 1965).…”
Section: Biochemical Phenotype and Antibiotic Resistance Profiles Of ...mentioning
confidence: 99%
“…Among the isolates harboring class 2 integron, only one contained a gene cassette comprising estX + sat2 + sat1. Previous studies have reported that the presence of gene cassettes associated with antimicrobial resistance indicates increased resistance rates (58,59) as well as increased potential for horizontal transfer (60).…”
Section: Discussionmentioning
confidence: 99%
“…The amplification program involved initial denaturation at 95°C for 2 min followed by 35 cycles of 95°C 30 sec, 55.4°C 60 sec, and 72°C 60 sec. 17 The sequences of the PCR products were obtained using the Sanger method and then were aligned with gene sequences from National Center for Biotechnological Information (NCBI) (https://www.ncbi.nlm.nih.gov/) to investigate for mutations.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%